The Role of Knowledge Sharing, Social Media, and Trust in Job Performance - Abdul Rohman (Universitas Mercu Buana, 2023)
The development of technological progress is the focus of the company's attention to survive in the era of competition. Technology is a key to winning the competition. Unfortunately, many human resources in the company cannot utilize technology properly. Social media is an excellent knowledge-sharing platform for now and can be used to improve job performance within an organization. Therefore, this study aims to measure the role of knowledge sharing, the use of social media and trust in employee performance at PT. XYZ. This research used a quantitative approach by gathering 128 respondents using non-probability sampling techniques with the census method. The data testing technique used in this study is SPSS 22.0. This study found that the use of social media in the workplace had a positive and significant effect on sharing knowledge, trust, and job performance. Meanwhile, knowledge sharing positively and significantly impacts job performance, and trust positively and significantly impacts job performance.